2015
DOI: 10.1371/journal.pone.0119192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Memory Complaints in Employed Compared to Non-Employed Aged 55–64 Years and the Role of Employment Characteristics

Abstract: ObjectivesTo examine the association of employment status and characteristics with prevalent and incident memory complaints (MC) in 55–64-year-olds.MethodsSubjects were participants of the Longitudinal Aging Study Amsterdam (LASA). Respondents with baseline data were selected to examine the association of employment status (n = 1525) and employment characteristics (n = 1071) with prevalent MC (i.e., MC at baseline). Respondents without MC at baseline were selected to examine the association of employment (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
(52 reference statements)
0
7
1
2
Order By: Relevance
“…Candidate variables were selected a priori based on clinical plausibility and/or previous research ( Table 1 ). 14 39 Data exploration suggested three ANCOVA analyses for bio-specimens (ANCOVA 1), brain measurements (ANCOVA 2) and cognition (ANCOVA 3) should be performed at each time-point. Prior to conducting ANCOVAs, collinearity was assessed through Belsley collinearity diagnostics 41 and any covariates found to have statistically significant associations with other covariates included in each ANCOVA were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Candidate variables were selected a priori based on clinical plausibility and/or previous research ( Table 1 ). 14 39 Data exploration suggested three ANCOVA analyses for bio-specimens (ANCOVA 1), brain measurements (ANCOVA 2) and cognition (ANCOVA 3) should be performed at each time-point. Prior to conducting ANCOVAs, collinearity was assessed through Belsley collinearity diagnostics 41 and any covariates found to have statistically significant associations with other covariates included in each ANCOVA were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Less physical activity, hypertension, smoking and depression were found to be associated with the increase occurrence of SCD (Paradise et al, 2011; Chen et al, 2014). Also, among workers, those with cognitively demanding work were more sensitive to the changes of cognitive decline, and were thus more likely to report SCD (Rijs et al, 2015). Moreover, Aarts et al (2011) demonstrated that SCD was related with multiple comorbidities (e.g., diabetes mellitus, stroke/transient ischemic attack, myocardial infarction, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Another longitudinal study performed by Rijs and colleagues in a population of employees aged 55-64, considering nonemployees as the control group, found that middle-aged workers are equally likely to experience memory complaints as nonworking age-peers, but on the other hand, among workers, those with cognitively demanding work were more likely to have memory complaints [30]. Jonsdottir and colleagues presented a case-control follow-up, testing the differences in the cognitive assessment of patients with stress-related exhaustion several years after they initially sought medical care [31].…”
Section: Resultsmentioning
confidence: 99%